AGAMA DAN ETNISITAS DALAM PEMILIHAN KEPALA DAERAH DI PROVINSI BENGKULU 2015 - Ifansyah Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
This study aims to explain the role of religion and ethnicity in winning political actors in the Bengkulu provincial elections, and the effectiveness of the role of religion and ethnicity in winning the candidate. Using political marketing theory, religion and ethnicity are packed into the backdrop of winning political actors. The positioning attitude and branding strategy that is right and mature, raises the political image in getting the sympathy of the community. The result of the research shows that first, the victory of Ridwan Mukti and Rohidin Mersyah have several factors, namely to do the right strategy positioning (candidate compactness, academic degree, mission vision and work program priority, politics politics, cultural preservation, not compartmentalization, harmonization of political elite, and uphold togetherness). Second, religion and ethnicity still as a strategy, but not dominant, its use is based only on the integrity of political actors, by packing Ridwan Mukti and Rohidin Mersyah as political actors who have both values. Thirdly, the principle of primordialism has decreased its effectiveness, so that to be used as the main strategy in electoral politics, especially Bengkulu Province Head Election, no longer has a significant impact like the previous year